Giant Appendiceal Leiomyosarcoma: A Rare and Unusual Tumour - Christine Natalia; Cherry E. Koh; Peter J. Lee (Case Reports in Surgery)
Appendiceal tumours are uncommon but may be present in 0.9–1.4% of all appendicectomy specimens. While carcinoid tumours and adenocarcinomas comprise the majority of appendiceal tumours, rarely, lymphomas or sarcomas may also present in the appendix. Appendiceal leiomyosarcomas are rare, and to date, only a handful of cases have been reported. The current paper presents a case of giant appendiceal leiomyosarcoma followed by a review of the literature.